A novel H395R mutation in MKKS/BBS6 causes retinitis pigmentosa and polydactyly without other findings of Bardet-Biedl or McKusick-Kaufman syndrome - Hulleman, John D. (Mol Vis, 2016)
PURPOSE: To identify the causative mutation in two siblings from a consanguineous family in India with retinitis pigmentosa (RP) and polydactyly without other findings of Bardet-Biedl syndrome (BBS). We also performed functional characterization of the mutant protein to explore its role in this limited form of BBS. METHODS: The siblings underwent a thorough ophthalmological examination, including retinal optical coherence tomography (OCT) imaging, and an extensive physical examination with abdominal ultrasonography to characterize the disease phenotype. Next-generation sequencing (NGS) using a panel targeting retinal degeneration genes was performed on genomic DNA samples from the siblings and parents. Upon identification of the causative mutation, functional characterization was accomplished by performing protein–protein interaction studies in human embryonic kidney (HEK-293T) and human adult retinal pigmented epithelium (ARPE-19) cells. RESULTS: The two siblings showed signs of RP and polydactyly. The patients did not have truncal obesity, renal anomalies, hydrometrocolpos, congenital heart disease, or overt cognitive defects. NGS identified a homozygous c.1184A>G mutation in the MKKS/BBS6 gene in both patients resulting in a p.H395R substitution in the MKKS/BBS6 protein. This mutant protein decreased the interaction of MKKS/BBS6 with BBS12 but did so to a different extent in the HEK-293T versus ARPE-19 cells. Nonetheless, the effect of the H395R variant on disrupting interactions with BBS12 was not as profound as other reported MKKS/BBS6 mutations associated with syndromic RP. CONCLUSIONS: We identified a novel H395R substitution in MKKS/BBS6 that results in a unique phenotype of only RP and polydactyly. Our observations reaffirm the notion that mutations in MKKS/BBS6 cause phenotypic heterogeneity and do not always result in classic MKKS or BBS findings.